1999
DOI: 10.1210/en.140.9.4133
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation of Promoter II- and Promoter 1f-Derived Cytochrome P450 Aromatase Transcripts in Equine Granulosa Cells during Human Chorionic Gonadotropin-Induced Ovulation: A Novel Model for the Study of Aromatase Promoter Switching

Abstract: Estradiol biosynthesis is a key biochemical trait of developing follicles. To study its regulation in equine follicles, the objectives of this study were to clone and determine the structure of equine cytochrome P450 aromatase (P450AROM), and characterize the regulation of P450AROM and P450 17␣-hydroxylase/C17-20 lyase (P45017␣) messenger RNAs (mRNAs) in vivo in equine preovulatory follicles isolated during hCGinduced ovulation. Two distinct P450AROM complementary DNAs (cDNAs) were isolated from an equine preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
4
25
0
Order By: Relevance
“…Despite these advantages, however, the information derived from rodents does not always serve as an accurate predictor of what occurs in large monoovulatory species. This has been demonstrated notably by a recent series of studies in equine preovulatory follicles, which showed that several genes involved in steroidogenesis and ovulation exhibit spatial and temporal expression patterns within the follicle that are different from what has been reported in rodents (Boerboom & Sirois 1998, Boerboom et al 1999, Kerban et al 1999a). The present study further emphasizes these differences by demonstrating distinct patterns of ovarian ADAMTS-1 and PR expression and regulation.…”
Section: Discussionmentioning
confidence: 89%
“…Despite these advantages, however, the information derived from rodents does not always serve as an accurate predictor of what occurs in large monoovulatory species. This has been demonstrated notably by a recent series of studies in equine preovulatory follicles, which showed that several genes involved in steroidogenesis and ovulation exhibit spatial and temporal expression patterns within the follicle that are different from what has been reported in rodents (Boerboom & Sirois 1998, Boerboom et al 1999, Kerban et al 1999a). The present study further emphasizes these differences by demonstrating distinct patterns of ovarian ADAMTS-1 and PR expression and regulation.…”
Section: Discussionmentioning
confidence: 89%
“…However, the information obtained from animal species does not always reflect the spectrum of potential expression among species. For example, in mares, follicular development and ovulation show several distinct characteristics that are not observed elsewhere: the Characterization and regulation of equine PGDH gonadotropin rise in preovulatory follicles induces a unique and remarkable modification of the granulosa cell layer in follicles prior to ovulation, characterized by extensive synthesis and assembly of a viscoelastic extracellular matrix (ECM) within the granulosa cell layer ) and the spatial and temporal regulation of several genes involved in ovulation and steroidogenesis in preovulatory follicles differs from those observed in the ovary of other mammals (Sirois et al 1991, Boerboom et al 1999. This difference in the pattern of gene regulation is further supported by the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Follicles were dissected into three cellular preparations referred to as the follicular wall (theca interna with attached granulosa cells), and isolated mural granulosa cells and thecal layers, as described (Sirois et al 1991). The relative purity of each cellular preparation is estimated to exceed 95% based on the selective expression of P450 17a-hydroxylase-C17-20 lyase (CYP17A1) and P450 aromatase (CYP19A1) mRNAs by theca interna and granulosa cells respectively (Boerboom et al 1999). Testicular tissues were obtained from the Hô pital de grandes animaux, Faculté de médecine vétérinaire (Université de Montréal) following a routine castration, whereas, other non-ovarian tissues were collected at a local slaughterhouse.…”
Section: Equine Tissues and Rna Extractionmentioning
confidence: 99%
“…Follicles were dissected into three cellular preparations referred to as the follicular wall (theca interna with attached granulosa cells), and isolated granulosa cells and thecal layers, as described (Sirois et al 1991). The relative purity of each cellular preparation is estimated to exceed 95% based on the selective expression of P450 17a-hydroxylase-C17-20 lyase (CYP17A1) and P450 aromatase (CYP19A1) mRNAs by theca interna and granulosa cells respectively (Boerboom et al 1999). Testicular tissues were obtained from the Large Animal Hospital of the Faculté de médecine vétérinaire (Université de Montréal) following a routine castration, whereas other non-ovarian tissues were collected at a local slaughterhouse.…”
Section: Equine Tissues and Rna Extractionmentioning
confidence: 99%